PENGARUH MINAT BELAJAR TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK SEKOLAH DASAR - Rina Indriani; Wahyudin; Turmudi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research was motivated by the low mathematical understanding abilities of elementary school students. The formulation of the problem in this research is: 1) Is there a positive correlation between learning interest scores and the acquisition of mathematical understanding abilities? 2) Does students' interest in learning have a positive effect on the acquisition of mathematical understanding abilities? The aim of this research is to determine the influence of interest in learning on students' mathematical understanding abilities. The research method used in this research is a quantitative method. The research instruments used were a learning interest questionnaire and a mathematical understanding ability test. Based on the results of data analysis and hypothesis testing using SPSS version 29.0 software, there is a significant positive correlation between learning interest scores and mathematical understanding ability scores, with a correlation coefficient value of 0.498, which means that it is 0.248 or 24.8% of students' mathematical understanding ability. determined by interest in learning. So it can be concluded that interest in learning has a positive effect on the mathematical understanding ability of elementary school students.